2012
DOI: 10.1007/jhep12(2012)030
|View full text |Cite
|
Sign up to set email alerts
|

Infinite-dimensional 3-algebra and integrable system

Abstract: The relation between the infinite-dimensional 3-algebras and the dispersionless KdV hierarchy is investigated. Based on the infinite-dimensional 3-algebras, we derive two compatible Nambu Hamiltonian structures. Then the dispersionless KdV hierarchy follows from the Nambu-Poisson evolution equation given the suitable Hamiltonians. We find that the dispersionless KdV system is not only a bi-Hamiltonian system, but also a bi-Nambu-Hamiltonian system. Due to the Nambu-Poisson evolution equation involving two Hami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…For the generators T n (36), we note that they are the associative operators with the product (37). According to the definition of the n-bracket (21), we get the following result.…”
Section: (Co)sine N-algebramentioning
confidence: 97%
See 2 more Smart Citations
“…For the generators T n (36), we note that they are the associative operators with the product (37). According to the definition of the n-bracket (21), we get the following result.…”
Section: (Co)sine N-algebramentioning
confidence: 97%
“…Let us turn to the case of 3-algebra. Substituting the generators (36) into the operator Nambu 3-bracket (18) and using (37) and (38), by direct calculation, we may derive the following 3-algebra:…”
Section: Q-deformed V-w N-algebramentioning
confidence: 99%
See 1 more Smart Citation
“…For the W 1+∞ constraints (15), it is noted that the constraint operators (14) contain the operators increasing and preserving the grading. Let us now introduce the following operators in terms of the operators decreasing and preserving the grading:…”
Section: Let Us Introduce the Operatorsmentioning
confidence: 99%
“…Chen er al. [42] investigated the classical Heisenberg and w ∞ 3-algebras and established the relation between the dispersionless KdV hierarchy and these two infinite-dimensional 3-algebras. They found that the dispersionless KdV system is not only a bi-Hamiltonian system, but also a bi-Nambu-Hamiltonian system.…”
Section: Introductionmentioning
confidence: 99%